A study on legal issues in protecting the rights of education of aborigines in peninsula Malaysia / Abdul Faizzani Abdul Aziz … [et al.] - Abdul Aziz, Abdul Faizzani; Mohd Yaakob, Mohamad Affan; Ghazali, Muhammad Hasif; Yahya, Nurul Faraheen (2012)
This research analysed the current situation of the rights of education of the Aborigines in Peninsular Malaysia where the Federal Constitution, the Aboriginal Peoples Act 1954 and the Education Act 1996 will be critically examine to identified the flaws. Then, the local laws will be compared to Education Act 2004 of Australian Capital Territory where this Act provides a better safeguard for the rights of education of the Aborigines in their country and international and national instruments are also analysed to identify guidelines which may be adopted to our local laws. The first chapter laid down the essence and structures of the research. While, the second chapter focused on the theories where rights of education in the Federal Constitution, Aboriginal Peoples Act 1954 and Education Act 1996 be examined whereby these flaws contribute to the failure in protecting the rights of education of the Aborigines. The third chapter discussed on the international instruments that provides guidelines for the rights of education of the Aborigines which may be incorporated in the domestic and national instruments that can be used as platforms to provide the rights of education of the Aborigines. In the fourth chapter, the researchers extracted the information gathered based on the interview conducted. Lastly, chapter five concluded the research where some recommendations are proposed in order to improve and to ensure that the right of education of the Aborigines is adequately protected.